2013
DOI: 10.1073/pnas.1309353110
|View full text |Cite|
|
Sign up to set email alerts
|

Improved El Niño forecasting by cooperativity detection

Abstract: The authors note that: "Due to a minor technical error in the calculation of the climatological average of the considered atmospheric temperatures for each calendar day, Figs. 2 and 3 appeared incorrectly. The amended figures and their legends are provided below. The main message and the interpretation of our paper remain unaffected by this correction." "The figures in the Supporting Information have been exchanged accordingly. We'd like to add that for the calculation of the climatological average, the leap d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
152
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 162 publications
(155 citation statements)
references
References 31 publications
(45 reference statements)
3
152
0
Order By: Relevance
“…31 high-quality atmospheric temperature data for the 1950-2011 period. The optimized algorithm (Data and Methods) involves an empirical decision threshold Θ.…”
Section: Forecasting the Next El Niñomentioning
confidence: 99%
See 1 more Smart Citation
“…31 high-quality atmospheric temperature data for the 1950-2011 period. The optimized algorithm (Data and Methods) involves an empirical decision threshold Θ.…”
Section: Forecasting the Next El Niñomentioning
confidence: 99%
“…In the first part , which represents the learning phase, all thresholds above the temporal mean of SðtÞ are considered, and the optimal ones, i.e., those ones that lead to the best predictions in the learning phase, are determined. We found that Θ-values between 2.815 and 2.834 lead to the best performance (31). In the second part of the data set (1981-2011), which represents the prediction (hindcasting) phase, the performance of these thresholds was tested.…”
Section: Forecasting the Next El Niñomentioning
confidence: 99%
“…35. The climate network approach has been found to be useful in improving our understanding of El Niño (8,(23)(24)(25) and in forecasting it (15,16). However, that approach has not been developed and applied to study systematically the global impact of El Niño, and that is what we try to achieve in quantitative terms here.…”
mentioning
confidence: 99%
“…These networks have been used successfully to analyze, model, understand, and even predict climate phenomena (6-16). Specific examples of climate network studies include the investigation of the interaction structure of coupled climate subnetworks (17), the multiscale dependence within and among climate variables (18), the temporal evolution and teleconnections of the North Atlantic Oscillation (19,20), the finding of the dominant imprint of Rossby waves (21), the optimal paths of teleconnection (22), the influence of El Niño on remote regions (8,23,24), the distinction of different types of El Niño events (25), and the prediction of these events (15,16). A network is composed of nodes and links; in a climate network, the nodes are the geographical locations, and the links are the correlations between them.…”
mentioning
confidence: 99%
“…20 It has been already successfully used in a wide variety of applications, ranging from the complex structure of teleconnections in the climate system, 15,18,49 including backbones and bottlenecks, 19,89 to dynamics and predictability of the El Niño-Southern Oscillation (ENSO). 66,92,93 Climate networks (class climate.ClimateNetwork) represent strong statistical interrelationships between time series and are typically reconstructed by thresholding the matrix of a statistical similarity measure S (Fig. 8) …”
Section: B Climate Networkmentioning
confidence: 99%